Ruthenium-catalyzed deaminative hydrogenation of aliphatic and aromatic nitriles to primary alcohols - Molnár, István G.; Calleja Ramos, Pilar; Hashmi, A. Stephen K.; Schaub, Thomas (ChemCatChem, 2017)
The deaminative hydrogenation of nitriles towards alcohols is a useful reaction to transform nitriles into alcohols with NH3 as the sole byproduct. Using the simple and robust RuHCl(CO)(PPh3)3 complex as a catalyst, at low H2 pressures a series of aliphatic and aromatic nitriles could be transformed into the corresponding alcohols. Suitable solvent systems for these reactions were 1,4-dioxane/water and EtOH/water mixtures. In most cases, the selectivity for the alcohols was excellent, and the corresponding amines were formed only in trace amounts.
Gesehen am 25.04.2018